Determinants of awareness, value perception, and societal support for sexual and reproductive health services among in-school adolescents in South-eastern Nigeria - Irene Ifeyinwa Eze; Chinyere Ojiugo Mbachu; Ifunanya Clara Agu; Ifeyinwa Chizoba Akamike; Godstime Eigbiremolen; Obinna Onwujekwe (BMC, 2023)
Abstract Background Adolescents are vulnerable to sexual and reproductive health (SRH) risks yet, have poor utilisation of SRH services due to personal, social, and demographic influences. This study aimed to compare the experiences of adolescents that had received targeted adolescent SRH interventions and those that did not and evaluated the determinants of awareness, value perception, and societal support for SRH service utilisation among secondary school adolescents in eastern Nigeria. Methods We undertook a cross-sectional study of 515 adolescents in twelve randomly selected public secondary schools, grouped into schools that had received targeted adolescent SRH interventions and those that did not, across six local government areas in Ebonyi State, Nigeria. The intervention comprised training of schools' teachers/counsellors and peer educators and community sensitisation and engagement of community gatekeepers for demand generation. A pre-tested structured questionnaire was administered to the students to assess their experiences with SRH services. Categorical variables were compared using the Chi-square test, and predictors were determined through multivariate logistic regression. The level of statistical significance was determined at p < 0.05 and a 95% confidence limit. Results A higher proportion of adolescents in the intervention group, 126(48%), than in the non-intervention group, 35(16.1%), were aware of SRH services available at the health facility (p-value < 0.001). More adolescents in the intervention than the non-intervention group perceived SRH services as valuable- 257(94.7%) Vs 217(87.5%), p-value = 0.004. Parental/community support for SRH service utilisation was reported by more adolescents in the intervention group than in the non-intervention group- 212 (79.7%) Vs 173 (69.7%), p-value = 0.009. The predictors are (i) awareness-intervention group (β = 0.384, CI = 0.290-0.478), urban residence (β=-0.141, CI=-0.240-0.041), older age (β-0.040, CI = 0.003-0.077) (ii) value perception - intervention group (β = 0.197, 0.141-0.253), senior educational class (β = 0.089, CI = 0.019-0.160), work-for-pay (β=-0.079, CI=-0.156-0.002), awareness (β = 0.192, CI = 0.425-0.721) (iii) parental/community support - work-for-pay (β = 0.095, CI = 0.003-0.185). Conclusions Adolescents' awareness, value perception, and societal support for sexual and reproductive health services were influenced by the availability of SRH interventions and socio-economic factors. Relevant authorities should ensure the institutionalisation of sex education in schools and communities, targeting various categories of adolescents, to reduce disparity in the utilisation of sexual and reproductive health services and promote adolescents' health.